2017
DOI: 10.1104/pp.17.00584
|View full text |Cite
|
Sign up to set email alerts
|

Adaptor Protein-3-Dependent Vacuolar Trafficking Involves a Subpopulation of COPII and HOPS Tethering Proteins

Abstract: ORCID IDs: 0000-0001-6345-6855 (J.-G.W.); 0000-0002-3501-5857 (Y.Z.).Plant vacuoles are versatile organelles critical for plant growth and responses to environment. Vacuolar proteins are transported from the endoplasmic reticulum via multiple routes in plants. Two classic routes bear great similarity to other phyla with major regulators known, such as COPII and Rab5 GTPases. By contrast, vacuolar trafficking mediated by adaptor protein-3 (AP-3) or that independent of the Golgi has few recognized cargos and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 43 publications
1
52
0
1
Order By: Relevance
“…We complemented the ap-3m-3 mutant expressing 35S:GFP-SUC4 with the wild-type 5.0-kb AP3M genomic fragment (COM AP3M ) or the 5.0-kb AP3M genomic fragment harboring the 3A mutation (COM AP3M-3A ) and observed the localization of GFP-SUC4. Consistent with previous findings (27,28), the tonoplast localization of SUC4 was abolished in the ap-3m-3 mutant ( Fig. 7C and SI Appendix, Fig.…”
Section: F-actin Binding Activity Of Ap3m Is Required For Maintainingsupporting
confidence: 92%
See 2 more Smart Citations
“…We complemented the ap-3m-3 mutant expressing 35S:GFP-SUC4 with the wild-type 5.0-kb AP3M genomic fragment (COM AP3M ) or the 5.0-kb AP3M genomic fragment harboring the 3A mutation (COM AP3M-3A ) and observed the localization of GFP-SUC4. Consistent with previous findings (27,28), the tonoplast localization of SUC4 was abolished in the ap-3m-3 mutant ( Fig. 7C and SI Appendix, Fig.…”
Section: F-actin Binding Activity Of Ap3m Is Required For Maintainingsupporting
confidence: 92%
“…Studies in mammalian cells have revealed that: 1) The β3 subunit of the AP3 complex interacts with the clathrin heavy chain via its C domain (21); 2) the δ-subunit is important for the recruitment of this complex to the membrane (20), while the δ-subunit interacts with the σ-subunit to recognize dileucine-based sorting signals (DE[XXXL]LI) (22); and 3) the μ-subunit binds to tyrosine-based sorting signals (YXXΦ) (23). In plants, defects in the AP3 complex lead to aberrant vacuole morphology (24)(25)(26) and abnormal protein trafficking, with most protein retained in the Golgi apparatus, such as SUC4 (27) and PAT10 (28), in root epidermal cells and embryo cells. Therefore, the AP3 complex is crucial for plant development and various cellular activities, especially for the proper functioning of the Significance Actin filament dynamics and the proper functioning of adaptor complexes are required for the sorting of cargo proteins from the Golgi to the vacuole, but the relationship between these 2 important processes remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For constructs used in subcellular localization, the coding sequences of CGF1, CGF2, and various mutant forms were amplified with the following primer pairs: ZP4997/ ZP4998 for CGF1, ZP5738/ZP5739 for CGF2, ZP4997/ ZP9786 for CGF1 SP , ZP5738/ZP9784 for CGF2 SP , ZP9787/ZP4998 for CGF1 ΔSP , and ZP9785/ZP5739 for CGF2 ΔSP . The resultant entry vectors were used in LR reactions with the destination vector Pro UBQ10 :GW-GFP [24] or Pro 35S :GW-GFP [25] to generate expression vectors, including Pro UBQ10 :CGF1-GFP, Pro UBQ10 :CGF2-GFP, Pro 35S :CGF1 SP -GFP, Pro 35S :CGF2 SP -GFP, Pro 35S :CGF1 ΔSP -GFP, and Pro 35S :CGF2 ΔSP -GFP.…”
Section: Dna Manipulationmentioning
confidence: 99%
“…More recently, TGN-localized AP1 g-adaptins were found to mediate the targeting of membrane proteins with di-Leu motifs to the tonoplast (Wang et al, 2014). Intriguingly, Arabidopsis AP3 has been implicated in a TGN-bypass pathway that transfers cargo directly from Golgi cisternae to the vacuole and is facilitated by the HOPS-tethering complex (Feraru et al, 2010;Zwiewka et al, 2011;Feng et al, 2017). Perhaps with the exception of AP2, which operates in clathrin-mediated endocytosis at the plasma membrane (Krauss et al, 2006;Di Rubbo et al, 2013), a function in vacuolar transport appears to be the norm among Arabidopsis AP complexes.…”
Section: Adaptinsmentioning
confidence: 99%